"Zal portuario de borde costero", plataforma de exportación del producto nacional. Proyecto arquitectónico (2018)
Zal Portal of Coordinal Edge, work of degree to choose the title of architect, by means of which 3 urban strategies of different radius of action are proposed, to be able to realize an architectural proposal, that will have a public, commercial, business use, through the business cluster function; the port ZAL proposes innovative constructive systems, in materials, in space and in design of the urban form and structure that it proposes, working from the action undid to a regional impact, making use of the logistic and port administration of the city of Cartagena.